2019
DOI: 10.1126/science.aax4092
|View full text |Cite
|
Sign up to set email alerts
|

Millennial storage of near-Moho magma

Abstract: The lower crust plays a critical role in the processing of mantle melts and the triggering of volcanic eruptions by supply of magma from greater depth. Our understanding of the deeper parts of magmatic systems is obscured by overprinting of deep signals by shallow processes. We provide a direct estimate of magma residence time in basaltic systems of the deep crust by studying ultramafic nodules from the Borgarhraun eruption in Iceland. Modeling of chromium–aluminum interdiffusion in spinel crystals provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 90 publications
0
33
0
Order By: Relevance
“…Some previous studies of the likely duration of basalt storage in the Icelandic crust are consistent with this time scale, but are poorly constrained [71,72]. Intriguingly, more detailed storage time scales have recently been obtained by the modelling of diffusion profiles in spinel inclusions from Borgarhraun, and indicate that crystals may be stored for about 1000 years in mushes prior to eruption [73].…”
Section: Sill Thickness Mush Thickness and Time Scalesmentioning
confidence: 86%
See 1 more Smart Citation
“…Some previous studies of the likely duration of basalt storage in the Icelandic crust are consistent with this time scale, but are poorly constrained [71,72]. Intriguingly, more detailed storage time scales have recently been obtained by the modelling of diffusion profiles in spinel inclusions from Borgarhraun, and indicate that crystals may be stored for about 1000 years in mushes prior to eruption [73].…”
Section: Sill Thickness Mush Thickness and Time Scalesmentioning
confidence: 86%
“…Diffusive exchange of Mg-Fe through the liquid and crystals of the mush pile may account for the olivine distributions. Recent diffusion chronometry results also indicate that spinel inclusions in crystalline nodules in Borgarhraun have been stored for ∼ 1000 years after their inclusion in a crystal framework [73].…”
Section: Synthesis: Evolution Of a Lower Crustal Sillmentioning
confidence: 99%
“…The slow coupled diffusion of CaAl‐NaSi largely precludes erasing primary magmatic zonation within crystals this large, as Grove et al () found that it would take 250,000 years to erase CaAl‐NaSi oscillatory zoning at only 100 μm. Previous work on residence time of plagioclase crystals below mid‐ocean ridges suggests that they reside within the crust for tens (Costa et al, ) to thousands of years (Mutch et al, ). In addition, Lange et al () estimated the minimum ascent time from the MOHO to the crust for plagioclase megacrysts to be on the order of 2–10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Geochemistry, Geophysics, Geosystems (Mutch et al, 2019). In addition, Lange et al (2013) estimated the minimum ascent time from the MOHO to the crust for plagioclase megacrysts to be on the order of 2-10 days.…”
Section: /2019gc008638mentioning
confidence: 99%
“…Our models utilize recent advances in numerical diffusion approaches that address diffusion anisotropy by allowing for high resolution investigation of diffusing species in three dimensions (c.f., Shea et al 2015aLynn et al 2017;Krimer and Costa 2017;Mutch et al 2019). Previous studies have used the slowest and/or fastest crystal directions to provide maximum or minimum timescale estimates when modeling in one dimension (1D; e.g., Pan and Batiza 2002;Longpré et al 2014;Thoraval and Demouchy 2014).…”
Section: Numerical Model Setupmentioning
confidence: 99%